Kedudukan Surat Kuasa Menjual dalam Perjanjian Utang Piutang dengan Wanprestasi - Destiarany, Regina; Anggriani, Reni (Universitas Muhammadiyah Yogyakarta, 2024)
A power of attorney is a letter document whose content is to give authority to other parties to do something that the power of attorney wants. Power of attorney is often given in carrying out certain legal actions, including making payments of debts and receivables. Debts and receivables in daily life are not new, especially in the business field which is used to increase capital or other things for the smooth running of business. The issue raised is how the position of the power of attorney in the debt and receivables agreement in default with a case study of Decision Number 33/PDT. G/2023/PN SPT. The method used is the normative method. The position of the power of attorney to sell in debts and receivables associated with the existence of default is inappropriate, what should be used in debts and receivables is the right of guarantee over land against these debts. The results of this study show that the making of a power of attorney in the aquo case is inappropriate, because the aquo case that occurs is a debt-receivables agreement, not a sale and purchase